NEW NORMAL BAGI PARIWISATA BALI DI MASA PANDEMI COVID 19 - Ida Bagus Gede Paramita; I Gede Gita Purnama Arsa Putra (UHN IGB Sugriwa Denpasar, 2020)
Covid 19 pandemic is a plague that changes the order of people's lives around the world otherwise it is called the new normal. The people are required to live in a new normal life with the intention that they can maintain their mental health and safety. Covid 19 has a very serious impact on the economy, especially those who rely on the economy in the tourism sector. The unavailability of the antivirus for Covid 19 which has not discovered yet increases the anxiety of the people to do their activities. For this reason, the government adopted a policy of implementing new normal life in carrying out ordinary activities outside the home by implementing permanent protections to prevent the spread of Covid 19. The purpose of this study a) to see the fluctuation of tourist visits to Bali before the pandemic; b) compared with tourist visit levels during the pandemic and; c) looking at the strategies of various stakeholders in recovering Bali tourism. This research data collection method is literature study, with secondary data. The results of this study see several strategies for restoring Bali tourism in the new normal, including applying adequate hygiene and safety standards for tourists, providing alternative travel patterns: staycation, niche tourism, solo travel tours, wellness tours, virtual tourism.